PEMANFAATAN METODE POSE ESTIMATION DAN MULTILAYER PERCEPTRON DALAM PENGEMBANGAN PEMBELAJARAN MANDIRI SENI BELADIRI TAEKWONDO - Irzan Fajari Nurahmadan (2021)
Taekwondo is a martial art from South Korea that has been developing in Indonesia since 1975 in North Jakarta. Since then Taekwondo has become increasingly popular, it can be seen when Taekwondo entered the official sport in the XI PON arena in 1985, due to the popularity of Taekwondo many instructor have built Taekwondo learning clubs throughout Indonesia, not only that the championship for Taekwondo has also increased rapidly in Indonesia and. Due to the large number of championships, many Taekwondo clubs carry out intensive training to train young athletes to participate in the championship, but the training is considered less than optimal due to the large number of students participating in the training which makes the instructor pay less attention, In order to solve the problem the author has an idea to build an independent learning system using the Pose Estimation method which is used so that the computer can recognize Taekwondo movements and Multilayer Perceptron with Backpropagation learning which is used to predict Taekwondo movements. This study uses primary data obtained from the DAS (Dynamic Able Success) club which contains two kicks and two blocks. This study obtained the most optimal accuracy of 100%.